Institutional Transformation and Digital Adaptation of Radio Republik Indonesia (RRI) Medan as a Public Broadcasting Institution (1998-2014) - Isra' Pasu Mutiara; Budi Agustono; Pujiati Pujiati (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study analyzes the institutional transformation of Radio Republik Indonesia (RRI) Medan, a public broadcasting institution, during the post-Reformasi period, focusing on how the organization responded to declining relevance and competitiveness amid media liberalization and accelerating digitalization. The main objective of this research is to examine the processes of institutional repositioning, changes in broadcasting practices, and strategic adaptations undertaken by RRI Medan in response to increasing competition from private radio and digital media between 1998 and 2014. Employing an institutional history approach, this study uses historical methods encompassing heuristic exploration, source criticism, interpretation, and historiography, supported by archival records, broadcasting policy documents, academic literature, and selected oral sources from RRI practitioners. The findings demonstrate that RRI Medan faced significant external pressures following its transition from a state-controlled radio to a public broadcasting institution. These pressures stimulated institutional restructuring, redefinition of public service functions, adjustments in broadcast content and listener segmentation, and the initial adoption of digital strategies through streaming and online platforms. However, these adaptive efforts were constrained by bureaucratic inertia, limited technological infrastructure, and human resource capacity. This study argues that the period 1998–2014 constitutes a critical transitional phase that laid the institutional foundation for RRI Medan’s shift toward a multi-channel public broadcasting model in the digital era. Scientifically, this research contributes to the historiography of Indonesian media by providing an empirical analysis of the transformation of public broadcasting at the local level, highlighting the interaction among institutional change, media policy, and digital disruption in post-authoritarian Indonesia.